2018
DOI: 10.2215/cjn.09350817
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization after Acute Kidney Injury in the Pediatric Intensive Care Unit

Abstract: AKI is independently associated with higher hospitalizations and physician visits postdischarge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 30 publications
(27 reference statements)
2
42
0
Order By: Relevance
“…21 In noncardiac surgery children admitted to the intensive care unit, AKI has been shown to be associated with increased health care use, including postdischarge hospitalizations, physician visits, and other important health outcomes. 8,22,23 Therefore, given the known strong association of AKI with readmission and other outcomes in non-cardiac surgery populations, these findings are notable. Children undergoing cardiac surgery are at high risk of readmission, which prompts an urgent need to find easily identifiable, strong predictors that would allow for targeted interventions to reduce readmission.…”
Section: Discussionmentioning
confidence: 92%
“…21 In noncardiac surgery children admitted to the intensive care unit, AKI has been shown to be associated with increased health care use, including postdischarge hospitalizations, physician visits, and other important health outcomes. 8,22,23 Therefore, given the known strong association of AKI with readmission and other outcomes in non-cardiac surgery populations, these findings are notable. Children undergoing cardiac surgery are at high risk of readmission, which prompts an urgent need to find easily identifiable, strong predictors that would allow for targeted interventions to reduce readmission.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with pAKI had higher rates of AKI in the 6 months prior to transplant and had more episodes of AKI in the first 12 months post‐transplant. Hessey et al 26 have shown that patients who develop AKI are more likely to be hospitalized again after discharge from their index admission, even after adjusting for confounders. Other studies in adult patients show that up to a third of those who have an episode of AKI are likely to have at least one more episode and a significant number of patients experience multiple episodes of AKI 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is defined as an abrupt onset of kidney dysfunction. AKI occurs in 20-30% of the general pediatric intensive care (PICU) population and up to 50% in children following cardiac surgery (1)(2)(3)(4)(5)(6). Compared to children who do not develop AKI in the PICU, children with AKI are at higher risk of poor early outcomes, including mortality, receipt and longer duration of mechanical ventilation, and prolonged length of PICU and subsequent hospital stay (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%